Analisis Sistem Antrian pada Pelayanan Customer Service (Studi Kasus: PT Bank BRI Cabang Raha) - Sitti Rahmawati Findayani; Asrul Sani; Muh. Kabil Djafar (JOSTECH Journal of Science and Technology, 2023)
The purpose of this study is to find out the queuing model using the structure of the single phase multi-channel queue system in customer service at PT Bank BRI Raha Branch and find out how to complete the queue model on customer service at PT Bank BRI Raha Branch. This research was conducted with direct observation on customer service at Bank BRI Raha Branch. From the data obtained, a steady state test and a Chi-Square kindness test were carried out on arrival patterns and service patterns. Then complete the queuing model using the single phase multi channel queue system structure. The results of the analysis showed that the arrival of customers at Bank BRI Raha Branch was 630 customers with an arrival rate of 2 people per hour and a customer service rate of 5 customers per hour. The queuing system in customer service at Bank BRI Raha Branch follows the queue model which means that the Poisson distributed arrival rate and service time are exponential, the number of channels in the dual system (2 customer service with 1 queue line), the queue discipline used by First Come First Serve (those served are customers who arrive first), the number of incoming customers is not limited or infinite in the queuing system and the population size at the input source is infinite. Busy period opportunities as large as , the average number of customers waiting in the queue is person, the average number of customer in the system is person, the average time spent by a customer waiting is hours, the average time spent in the system including services is hours.